Letter from Arnold O. Beckman to S. S. Prentiss - Beckman, Arnold O. (1945)
Arnold Beckman discusses the status of contract reports, an instrument damaged during shipment, and asks about Spencer Prentiss's post-war plans. He expects to consult with Linus Pauling to decide which instrument to exhibit at the Museum of Science and Industry. Developed from a Linus Pauling design during WWII, the technology behind Beckman Instruments’ oxygen analyzers ended up doing such diverse jobs as monitoring astronauts’ respiration, maintaining packaged food safety, and preventing blindness in newborn babies.
Keywords: Scientific apparatus and instruments; Oxygen--Measurement; Oxygen--Analysis; Pauling, Linus, 1901-1994; Beckman Instruments, Inc.